Strategies and Implementation of Sustainable Economic Development by Local Governments: Challenges and Opportunities - Paramita, Ahsani; Syachbrani, Warka (Phinisi Applied Accounting Journal, 2025)
Sustainable economic development has become a global and national imperative, requiring active roles of local governments as frontline implementers. This article analyzes the roles, strategies, challenges, and opportunities faced by local governments in achieving sustainable economic development. Using qualitative literature review methodology, we examine regional policies, programs, and case studies. Results indicate that local governments play pivotal roles through environmentally based spatial planning, empowerment of green local MSMEs, sustainable tourism development, and circular economy principles. Key challenges include budget constraints, human resource capacity gaps, inter-institutional coordination issues, and short-term development pressures. However, significant opportunities exist through technology adoption, multi-stakeholder collaboration, and green fiscal incentives. We conclude that successful local sustainable economic development requires strong political commitment, supportive regulations, institutional capacity building, and active community-business participation. Keywords: Sustainable Economic Development, Local Government, Green Economy, Regional Policy, Regional Development, Sustainable MSMEs, Pembangunan ekonomi berkelanjutan telah menjadi imperatif global dan nasional, menuntut peran aktif pemerintah daerah sebagai ujung tombak pelaksana. Artikel ilmiah ini bertujuan untuk menganalisis peran, strategi, tantangan, dan peluang yang dihadapi pemerintah daerah dalam mewujudkan pembangunan ekonomi yang berkelanjutan. Metode penelitian yang digunakan adalah studi literatur dengan pendekatan kualitatif, mengkaji berbagai kebijakan, program, dan studi kasus di tingkat daerah. Hasil kajian menunjukkan bahwa pemerintah daerah memegang peran kunci melalui perencanaan tata ruang berbasis lingkungan, pemberdayaan UMKM berbasis lokal dan hijau, pengembangan pariwisata berkelanjutan, serta penerapan prinsip ekonomi sirkular. Tantangan utama meliputi keterbatasan anggaran, kapasitas SDM, koordinasi antar lembaga, dan tekanan pembangunan jangka pendek. Namun, peluang besar terbuka melalui pemanfaatan teknologi, penguatan kolaborasi multi-pihak, dan insentif fiskal hijau. Artikel ini menyimpulkan bahwa keberhasilan pembangunan ekonomi berkelanjutan di tingkat daerah memerlukan komitmen politik kuat, regulasi yang mendukung, peningkatan kapasitas kelembagaan, serta partisipasi aktif masyarakat dan dunia usaha. Kata kunci: Pembangunan Ekonomi Berkelanjutan, Pemerintah Daerah, Ekonomi Hijau, Kebijakan Daerah, Pembangunan Wilayah, UMKM Berkelanjutan